Air transport networks of global integrators in the more liberalized Asian air cargo industry. (August 2019) - Malighetti, Paolo; Martini, Gianmaria; Redondi, Renato; Scotti, Davide
Abstract: Driven by the impressive growth of Chinese e-commerce, Asia Pacific is expected to become the world's largest regional parcel market in the near future. However, it was only after 2003–2004 that global integrated carriers gained the necessary traffic rights to establish hubs in China. This development led to a significant reshaping of the Asian air networks and has produced the current configurations. The aim of this paper is to provide an analysis of such configurations by graphical analysis and complex network metrics. Our results show that DHL, FedEx, and UPS operate extensive multi-hub networks while the TNT network is quite limited. This finding suggests a general need for flexibility and robustness in a context of changing regulations and still-imperfect market liberalization. This need, however, has been addressed with different strategies. DHL (whose network exhibits the highest centralization and the lowest density) focuses more on the efficiency of its air network, while FedEx and UPS rely more on robustness but in different ways (i.e., in the case of FedEx, the highest transitivity combined with a lower centralization while UPS relies on the lowest centralization combined with the highest density). Moreover, airports' centrality indices confirm the central role gained by Chinese airports as a result of the change in the Chinese aviation policy. Such airports lay on a remarkable number of shortest paths that connect couples of other airports in the three networks. Finally, we provide an interpretation of our results in a policy perspective and indicate the possibility of a re-configuration of integrators' air networks toward a more efficient structure if Asian governments implement policy interventions that facilitate international trade, cooperation, and liberalization. Highlights: Asia Pacific is expected to become the world's largest regional parcel market in the near future. DHL, FedEx, and UPS operate extensive multi-hub networks while the TNT network is quite limited. Airports' centrality indices confirm the central role gained by Chinese airports. DHL focuses more on the efficiency of its air network, while FedEx and UPS rely more on robustness. There is the need for Asian governments interventions to facilitate international trade and cooperation.